Fractal Wavelet Coding Using A Rate-Distortion Constraint - Li, Jin; Kuo, C.-C. Jay (IEEE International Conference on Image Processing, Lausanne, Switzerland, 1996)
We propose a hybrid fractal wavelet coder (FWC) which adopts adaptive fractal prediction in the wavelet domain and wavelet coding in this research. This new compression scheme uses wavelet coding as the core component, and applies contractive mapping (or the so-called fractal prediction) whenever it offers additional rate savings. A model based rate-distortion (R-D) criterion of low complexity is used to evaluate the fractal prediction efficiency and search for the best domain-range match. The superior R-D performance of FWC is demonstrated with extensive experimental results.